RECENT ADVANCES AND FUTURE PROSPECTS OF NON-INVASIVE INSULIN DELIVERY SYSTEMS - AL-TABAKHA, MOAWIA M.; MUBARA, SALWA SAMI; AZEEZ, BALSAM SAAD (International Journal of Applied Pharmaceutics, 2019)
Non-invasive insulin delivery systems have been of global interest. The goal of many studies was to optimize suitable delivery formulation capable of producing comparable insulin bioavailability and safety that match or supersedes conventional delivery by the invasive subcutaneous (SC) injections. Historically, Pfizer marketed the first insulin inhaler Exubera® in 2006 which was later retracted from the market before completing the two years. In recent years, Afrezza®, a new inhalator, and Oral-Lyn™, a buccal spray, have been introduced to the market. While Afrezza® lost the marketing and distribution support from Sanofi, Oral-Lyn™ have not secured US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) marketing approval yet. Different technologies to improve insulin’s permeation and absorption through different routes are in the pipelines. This review discusses several non-invasive strategies that have been appropriately tested and duly approved by the FDA. Other delivery systems are in different phases of development, ranging from in vitro studies to phase 3 clinical trials, providing indications towards the prospects of next-generation delivery systems. This review covers studies published in the past 10 y using Scopus, Clinicaltrials.gov, PubMed and Google scholar databases. The outcomes of this review indicate that the door is still open for more innovative, efficient and convenient non-invasive insulin delivery systems than currently available which may take several years before we can see a game changer in the market.